Diagnostic significance of noncoding RNAs in kawasaki disease: A systematic review and meta-analysis - Zhong, Xiaoling; Jia, Xufeng; Wang, Hui; Chen, Guihua; Li, Hongxia; Li, Pingping; Yang, Taoyi; Xie, Jiang (Frontiers in Pediatrics, 2023)
Objective: Kawasaki disease (KD) is a systemic vasculitis disease, and early effective intervention would reduce the occurrence of coronary artery lesions (CALs). Recently, many scholars have been committed to studying the relationship between noncoding RNAs and KD. This systematic review aimed to analyze the diagnostic value of noncoding RNAs(ncRNAs) in distinguishing different KD status. Methods: We searched for the diagnostic values of ncRNAs in KD in CNKI, VIP, Wanfang, China Biomedical Literature Database as well as PubMed, Web of Science, Embase, and Cochrane Library up to April 15, 2022. Included studies were further analyzed using STATA 12.0, Meta-disc 1.4 and RevMan and Manager 5.4 software. Results: A total of six studies investigating the diagnostic performance of ncRNAs in differentiating KD-CAL (n=101) from KD-NCAL patients (n=123) were included in this this meta-analysis. The calculated area under the curve(AUC) was 0.83 (0.80–0.86). Four studies on the diagnostic performance of ncRNAs in differentiating acute KD patients (n=139) from convalescent KD patients (n=109) were included. The calculated AUC was 0.87 (0.84–0.90). Four studies focused on the diagnostic performance of ncRNAs combined with other laboratory indexes in KD by assessing 137 KD patients and 152 febrile controls. The calculated AUC was 0.90 (0.87–0.92). Four studies assessed the diagnostic performance of ncRNAs in differentiating intravenous immunoglobulin (IVIG)-resistant KD patients from IVIG-responsive KD patients. The calculated AUC was 0.9135±0.0307. These results indicated that ncRNAs have good diagnostic efficacy in KD. Conclusions: This meta-analysis showed that ncRNAs have potential as a biomarker for distinguishing different KD status. However, since limited studies were included in this meta-analysis, larger and well-designed diagnostic studies should be conducted to validate these results.